Junk Food Consumption and its Association with Anthropometric Indices among undergraduates in Nigeria - Obasi, N.A.; Ogundapo, S.S.; Nweze, E.; Obasi, S.E.; Egwu, C.O. (Journal of Pharmacy and Nutrition Sciences, 2019)
Junk foods consumption in institutions of higher learning has increasingly become an important part of students’ diet in Nigeria. This study was carried out to determine the pattern of junk food consumption among students in higher institutions of learning and the association between the junk food consumption and anthropometric indices measuring body weight status. A total of 900 students comprising 450 male and 450 female volunteers, aged 17 to 33 years were recruited from Akanu Ibiam Federal Polytechnic Unwana, Nigeria for the study. Seventy-nine percent of the students affirmed that the actually enjoy junk food. A total of 33.89% reported eating junk food everyday while 36.44% usually eat it at school during lunch with convenience been stated as the main reason for this consumption pattern by majority (48.44%). Low prevalence of obesity was observed i.e. 1.67% and 2.44% using body mass index (BMI) and waist-hip ratio (WHR), respectively, while majority of the volunteers i.e. 81.33% and 82.78% had normal BMI and WHR, respectively. There was no significant (P > 0.05) association between consumption of junk foods, frequency of consumption and body mass index or waist-hip ratio. This study revealed that there is no body weight status danger in junk food consumption pattern among the students. Thus, students may continue in their consumption pattern of this specified junk food if it is convenient and if it may enable them to meet up with their lined-up activities in the campus.